Interactive Job Involvement and Organizational Commitment on Job Turnover Revisited - Sureshkumar, C. (Journal of Current Computer Science and Technology, 2014)
Apathetic employees constitute one of four employee categories in Blau and Boalâ€™s (1999) model. Six sensitivity analyses were applied to create positive and negative changes in the measurement scores on job involvement and affective commitment of 553 employees to determine which variable produced the greatest Apathetic employee mobility. While changing both variables simultaneously created the greatest movement, on an individual basis, changing affective commitment produced greater Apathetic employee mobility than changing job involvement. The managerial implications of these findings are discussed. Â Keywords: Apathetic, employee, measurement, mobility